Analisis Perbedaan Kadar Kolesterol Berdasarkan Status Hipertensi PadaPekerja Pelabuhan di Tanjungpinang, Kepulauan Riau - sianipar, agustina (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2026)
Non-communicable diseases (NCDs), particularly hypertension and dyslipidemia, are a growing global health problem for workers. Port workers have specific risk factors, such as irregular physical activity patterns and high-fat consumption, which can affect blood pressure and cholesterol levels. This study aims to determine differences in cholesterol levels between hypertensive and non-hypertensive port workers in the Tanjungpinang Port work area in 2025. This study used a cross-sectional design using secondary data from NCD screening conducted by the Tanjungpinang Class I Health Quarantine Center in 2025. The dependent variable was cholesterol level, while the independent variables included hypertension status, age, gender, and body mass index (BMI). The study sample consisted of all screening participants with complete data; workers with incomplete data were excluded. Data analysis used the Mann–Whitney U test due to non-normal distribution of the data. A total of 612 workers participated in NCD screening, with a hypertension prevalence of 32.84% of the 612 workers, 32.84% had hypertension and 54.08% had high cholesterol levels. Most participants were male (63.2%) and overweight (67.8%). Mann–Whitney U test showed no significant difference in cholesterol levels between hypertensive and non-hypertensive workers (p=0.941). Significant differences in cholesterol levels were observed by sex (p<0.001) and age group (p=0.001). There was no significant difference in cholesterol levels between hypertensive and non-hypertensive port workers. Age and sex were more strongly associated with cholesterol levels and should be considered in cardiovascular risk screening programs. Keyword: Hypertension, cholesterol levels, non-communicable disease screening, port health services